Factors related to women's childbirth satisfaction in physiologic and routine childbirth groups - Elham Jafari; Parvin Mohebbi; Saeideh Mazloomzadeh (Wolters Kluwer Medknow Publications, 2017)
Background: Women's satisfaction with childbirth is an important measure of the quality of maternity care services. This study aims to address factors related to women's childbirth satisfaction in physiological and routine childbirth groups. Materials and Methods: This descriptive-analytical study was conducted among 340 women in physiological and routine childbirth groups in 2012. Women were selected through convenience sampling method in the routine group and by census in the physiological group. Data were collected using a 5-part questionnaire composed of demographic and obstetrics details, Mackey's Childbirth Satisfaction Rating Scale (CSRS), satisfied with birth setting, Labor Agentry Scale (LAS), and Visual Analogue Scale (VAS), which was completed by interview 24 hours after childbirth. Data were analyzed using the Statistical Package for the Social Sciences version 18 software using Pearson correlation test, independent t-test, analysis of variance, and linear, multivariate regression model at the significant level of P< 0.05. Results: In both the physiological and routine childbirth groups, satisfaction was found related to the severity of pain (P < 0.05), self-control (P < 0.0001), and birth setting satisfaction (P < 0.0001). In the physiological group, satisfaction was significantly related to previous knowledge of childbirth (P = 0.024), attitude toward the recent pregnancy (P = 0.007), and perceived severity of pain (P = 0.016). However, in the routine group, satisfaction was related only to intentional pregnancy (P = 0.002). In neither group, satisfaction was related to demographic characteristics, maternal parity, and participation in pregnancy and childbirth classes or maternal feelings toward the onset of childbirth (P > 0.05). Conclusions: Improved physical structure and setting of birth room, nonmedical pain relief, mothers' involvement in the process of labor, and sense of being in control are associated with mothers' satisfaction.